Geiko's negotiation on the Ie system in the film Hanaikusa - Putri, Sabrina Wanda; Puspitasari, Diana; Suryadi, Yudi (Universitas Dian Nuswantoro, 2024)
This research aims to describe how the geiko profession can serve as a form of women's negotiation within the ie system in the film Hanaikusa. The theory used in this research is the ie system. It is a qualitative descriptive study with data consisting of dialogues and screenshots that focus on geiko's negotiations with the ie system in the film Hanaikusa. The research employs the observation method and note-taking techniques in the data collection process. Data analysis techniques in this study include data reduction, data presentation, and conclusions. The results of the study indicate that there are 14 data on geiko's negotiations with the ie system, including 4 data on women's appearances (fuyo), 2 data on women's skills (fuko), 3 data on women's services and language (fugen), 3 data on women's moral values (futoku), and 2 data on unmarried women and child care. Based on the results of the data analysis, it can be concluded that the geiko profession, although not conforming to traditional female roles in the ie system, is capable of transcending the conventional values associated with women.